2018
DOI: 10.1016/s2468-1253(18)30119-5
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol for small bowel ulcers in patients with obscure bleeding taking aspirin and non-steroidal anti-inflammatory drugs (MASTERS): a randomised, double-blind, placebo-controlled, phase 3 trial

Abstract: National Health Service (NHS) Greater Glasgow and Clyde and NHS Ayrshire and Arran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Recently, Kyaw et al 21 performed an RCT of 84 aspirin users with small bowel bleeding who required aspirin therapy and found that misoprostol (200 µg given 4 times daily) for 8 weeks was superior to placebo in healing of small bowel ulcers. Similar results were also reported in another randomized trial by Taha et al 22 Though the potential protective effects of misoprostol were observed in these studies, large clinical trials with long-term outcomes are lacking. Furthermore, significantly increased risk of drug-related adverse effects like abdominal pain, nausea or vomiting, diarrhea and high dropout rate related to the use of misoprostol were observed in clinical trials.…”
Section: Misoprostolsupporting
confidence: 87%
See 1 more Smart Citation
“…Recently, Kyaw et al 21 performed an RCT of 84 aspirin users with small bowel bleeding who required aspirin therapy and found that misoprostol (200 µg given 4 times daily) for 8 weeks was superior to placebo in healing of small bowel ulcers. Similar results were also reported in another randomized trial by Taha et al 22 Though the potential protective effects of misoprostol were observed in these studies, large clinical trials with long-term outcomes are lacking. Furthermore, significantly increased risk of drug-related adverse effects like abdominal pain, nausea or vomiting, diarrhea and high dropout rate related to the use of misoprostol were observed in clinical trials.…”
Section: Misoprostolsupporting
confidence: 87%
“…Furthermore, significantly increased risk of drug-related adverse effects like abdominal pain, nausea or vomiting, diarrhea and high dropout rate related to the use of misoprostol were observed in clinical trials. 18,22…”
Section: Misoprostolmentioning
confidence: 99%
“…Furthermore, this drug also exerted a prophylactic effect against small intestinal lesions caused by a 2-week administration of diclofenac [23]. Recently, a randomized trial reported that misoprostol was effective in healing small-bowel ulcers [100]. However, this study recruited both NSAIDs and aspirin users with occult bleeding only.…”
Section: Misoprostolmentioning
confidence: 99%
“…Recently, a randomized trial reported that misoprostol was effective in healing small bowel ulcers (ulcer healing rate of 54%). 22 This study recruited both NSAIDs and aspirin users with occult bleeding only. Furthermore, it is unclear whether patients in this study continued aspirin or NSAIDs during the ulcer healing period.…”
Section: Discussionmentioning
confidence: 99%